Bibliometric analysis and visualization of research trends on HIV-1 capsid inhibitors (2000–2022) - Sun, Lin; Zhang, Tongchao; Xu, Shujing; Zhang, Xujie; Zhan, Peng; Liu, Xinyong (Frontiers in Pharmacology, 2023)
Acquired immunodeficiency syndrome (AIDS) has seriously endangered human life and health, the main pathogenic agent is human immunodeficiency virus type 1 (HIV-1). The combination antiretroviral therapy (cART) has shown serious drug resistance and side effects, and the discovery of HIV-1 capsid inhibitors is an effective way to solve the problem. Recent studies have shown significant progress in the research of HIV-1 capsid inhibitors. However, there is still a lack of comprehensive overview of bibliometric analysis in this field. This study aimed to provide the research trends and hotspots of HIV-1 capsid inhibitors.Publications related to HIV-1 capsid inhibitors from 2000 to 2022 were searched on the Web of Science Core Collection (WoSCC) database and screened according to inclusion criteria. VOSviewer was conducted to evaluate the results.96 publications from 25 countries were finally included, and the number of annual publications related to HIV-1 capsid inhibitors showed an increasing trend. The USA was the most productive country with the most publication number, H-index, and total citation number, as well as the widest international cooperation. The most popular journal in this field was Journal of Virology. Drexel University was the most productive institution, and Simon Cocklin participated in the most publications.Keywords co-occurrence analysis exhibited that studying the molecular mechanism of capsid protein, discovering drug candidates, and improving antiretroviral therapy are the main and hot topics in this field.This is the first bibliometric study in the field of HIV-1 capsid inhibitors, which comprehensively analyzed the research trends and hotspots in this direction. This work is expected to provide the scientific community with new insights to promote the research of HIV-1 capsid inhibitors.